2017
DOI: 10.1186/s12882-017-0498-5
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbic acid ameliorates renal injury in a murine model of contrast-induced nephropathy

Abstract: BackgroundContrast induced nephropathy (CIN) is the commonest cause of iatrogenic renal injury and its incidence has increased with the advent of complex endovascular procedures. Evidence suggests that ascorbic acid (AA) has a nephroprotective effect in percutaneous coronary interventions when contrast media are used. A variety of biomarkers (NGAL, NGAL:creatinine, mononuclear cell infiltration, apoptosis and RBP-4) in both the urine and kidney were assayed using a mouse model of CIN in order to determine whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…A relation between faltering and tissue fibrosis has actually been demonstrated in a prior rat model of diabetic nephropathy ( Hueper et al, 2012 ). According to another study by Rollins et al (2017) declines in FA likely stem from necrosis/apoptosis of medullary tubular epithelial cells, impairing water diffusion along tubular structures. Cheung et al (2010) have further acknowledged reduced renal medullary FA values 5 h after ischemia-reperfusion injury, accompanied by cellular edema and histologic evidence of necrosis.…”
Section: Discussionmentioning
confidence: 97%
“…A relation between faltering and tissue fibrosis has actually been demonstrated in a prior rat model of diabetic nephropathy ( Hueper et al, 2012 ). According to another study by Rollins et al (2017) declines in FA likely stem from necrosis/apoptosis of medullary tubular epithelial cells, impairing water diffusion along tubular structures. Cheung et al (2010) have further acknowledged reduced renal medullary FA values 5 h after ischemia-reperfusion injury, accompanied by cellular edema and histologic evidence of necrosis.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, Rollins et al . [22] in a murine model of CI-AKI observed that ascorbic acid reduced the urinary NGAL-to-creatinine ratio, which is indicative of the frequency and severity of the renal injury.…”
Section: Discussionmentioning
confidence: 99%
“…With the advancement of clinical treatment for CIN, drugs such as N‐acetylcysteine (NAC), 7 vitamin C 8 and statins 9 have been utilized. However, there is no strong evidence to prove that any drug can reduce the occurrence of CIN.…”
Section: Introductionmentioning
confidence: 99%